Peran Strategis Lembaga Penjaminan Mutu Pendidikan (LPMP) dalam Peningkatan Mutu Sekolah Jenjang SMA di Kota Yogyakarta - Hana Oktaviani, Avidonna (2017)
The aim of this research to describe the strategic of the role of Quality Assurance Institution (LPMP). The research is qualitative with an ethnographic design. Data collection techniques in this research are in-depth interviews, observation, and documentation. The interviewy are the Head of Quality Mapping and Supervision Division of LPMP DIY, Principal and Senior High School teacher in Yogyakarta. By triangulation techniques and resources. The technique date analysis is in the site. The results of this research are: 1) The Strategic Role of Education Quality Assurance Institution (LPMP) is technical assistance to Education, Youth and Sports Department through Internal Quality Assurance System (SPMI) at model schools and impact schools, 2) The obstacle which occur during the implementation of SPMI are, limited time and cost, lack of training off interviewes of the workshop, 3) Implementation of SPMI has an impact on two aspects, aspects of the process with the achievement of SPMI objectives at school model and the impact, so as to make quality assurance independently. Aspects of the outcome of SPMI's goal of improving the quality of the eight National Standards has not been seen, because it requires a long process, at least three years